The Effect of Management Support, Team Work, and Monitoring & Evaluation Process on Implementing the Patients Identification - Agatha Vivian Giovani, Agatha Vivian Giovani; Dewi, Sandra; Dian, Wahyuni (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: One of the efforts to fulfill patient safety targets is identifying patients correctly. Identification carried out incorrectly will have fatal consequences, triggering other errors. An important paradigm for reducing misidentification requires more than two patient identifiers. Objective: The study aims to analyze the influence of management support, team work, monitoring and evaluation process on implementing the patients’ identification among nurses at Wisma Rini Pringsewu Hospital. Method: We conduct the cross-sectional study to examine the causalities of independent variable with dependent variable. Result: Management support has a direct effect on the implementation of patient identification. Management support also has an indirect effect on the implementation of patient identification, through monitoring and evaluation. Meanwhile, monitoring and evaluation can have a direct influence on the implementation of patient identification. Team work influences the implementation of patient identification, but the influence is small, so monitoring and evaluation is needed so that team work works well. Meanwhile, team work is formed due to the contribution of management support. Implication: Create monitoring and evaluation policies related to the implementation of quality improvement and patient safety activities